2003
DOI: 10.1137/s1111111102412802
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic System Analysis for the Delay-Induced Hopf Bifurcation in the Wright Equation

Abstract: Abstract. We apply the synergetic elimination procedure for the stable modes in nonlinear delay systems close to a dynamical instability and derive the normal form for the delay-induced Hopf bifurcation in the Wright equation. The resulting periodic orbit is confirmed by numerical simulations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…Numerous examples exist where such a situation arise, especially in applications where the dynamics is subject to a delayed feedback component expressing a sigmoidal behavior. It has indeed been shown that the center manifold for a system with quadratic nonlinearity affects the deterministic dynamics [35]. The treatment of the cubic case is analogous to the one we perform here, and is presented elsewhere.…”
Section: Application To the Asymmetrical Transcritical Bifurcationmentioning
confidence: 73%
See 2 more Smart Citations
“…Numerous examples exist where such a situation arise, especially in applications where the dynamics is subject to a delayed feedback component expressing a sigmoidal behavior. It has indeed been shown that the center manifold for a system with quadratic nonlinearity affects the deterministic dynamics [35]. The treatment of the cubic case is analogous to the one we perform here, and is presented elsewhere.…”
Section: Application To the Asymmetrical Transcritical Bifurcationmentioning
confidence: 73%
“…In this section, we will introduce the notation and define the material required to perform the rather standard center manifold reduction of delayed functional differential equations. Reviews and in depth discussions of this method can be found in [30,31,34,35].…”
Section: A Analysis Of Autonomous Ddesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus our analytical result (27), (29) can be interpreted as the first terms within a spectral representation (33), where the frequency Ω = 2π/T and the Fourier coefficients c 0 , c 1 , c 2 are given by (28) and (30). Analyzing the Hopf bifurcation with a FFT, we numerically determinded Ω, c 0 , c 1 , c 2 as a function of the smallness parameter ε.…”
Section: Numerical Verificationmentioning
confidence: 99%
“…Chimera states, which were initially revealed and investigated in ensembles of coupled oscillators, have also been found in single oscillators with time-delayed feedback [29,30]. It is well-known that in the presence of time delay simple dynamical systems can exhibit complex behavior, such as delay-induced bifurcations [31], delayinduced multistability [32], stabilization of unstable periodic orbits [33] or stationary states [34], to name only a few examples. As noted in [35], there exists an analogy between the behavior of time-delayed systems and the dynamics of ensembles of coupled oscillators or spatially extended systems [36,38].…”
mentioning
confidence: 99%